Synthesis, characterization, and quantitative structure–activity relationship studies of bioactive dehydroacetic acid and amino ether Schiff base complexes. Issue 6 (9th September 2016) - Devi, Jai; Devi, Suman; Kumar, Ashwani
Abstract: Structural aspects of organosilicon(IV) and organotin(IV) complexes with dehydroacetic acid and amino ether Schiff base ligand have been described with the help of elemental analyses, conductance measurements, UV–Vis, infrared, multinuclear magnetic resonance, mass spectroscopy as well as thermogravimetric analysis, and X‐ray diffraction studies. Analysis of data suggested that the Schiff base provides two bidentate NO domains and was coordinated to silicon and tin moiety through the imine nitrogen and hydroxyl oxygen atom. Complexes were found to be nonelectrolytic and monomeric in nature. The thermal decomposition for tin compounds occurred in two steps and resulted into the formation of pure SnO2 as end product. The in vitro biological effects of the synthesized compounds were tested against two Gram‐positive and two Gram‐negative bacteria. The results of biological activity showed that all the complexes have enhanced activity as compared with the corresponding ligand, and compounds5, 9, 11, 12, 13, 15, 16, and17 were more potent than the standard drug ciprofloxacin. Compound17 exhibited best antibacterial activity with lowest minimum inhibitory concentration value and maximum zone of inhibition. Further, quantitative structure–activity relationship studies pointed out that more stable compound were more active as antibacterial agents.